Analysis of clinical factors affecting pregnancy outcomes after embryo transfer in patients with intrauterine adhesions - Liu, Jing; Chen, Hui; Lin, BeiBei; Wang, Chen; Ban, DeYing; Zhong, XiaoYing; Sun, HongXiang (Frontiers in Medicine, 2025)
ObjectiveThis study aimed to investigate factors influencing embryo transfer success rates after hysteroscopic adhesiolysis in patients with intrauterine adhesions (IUAs).MethodsA retrospective analysis was conducted on the clinical data of 2,447 patients who underwent hysteroscopy and were diagnosed with intrauterine adhesions (IUAs) at our center from January 2023 to December 2023. All patients received adhesion separation surgery and underwent embryo transfer through assisted reproductive technology (ART) after the operation. The patients were divided into the non-pregnancy group (n = 955) and the pregnancy group (n = 1,492) based on pregnancy outcomes. The baseline characteristics, degree of intrauterine adhesions, type and duration of balloon placement, time interval from surgery to embryo transfer, number and type of transferred embryos, quality of transferred embryos, and endometrial thickness before transfer were compared between the two groups. Univariate and multivariate regression analysis methods were performed to identify factors affecting the success rate of embryo transfer.ResultsUnivariate analysis revealed significant associations between pregnancy outcomes and the followinf factors: age (OR = 0.91, p < 0.001), anti-Müllerian hormone (AMH, OR = 1.06, p < 0.001), infertility duration (OR = 0.96, p = 0.044), severe degree of intrauterine adhesion (OR = 0.47, p = 0.001), balloon placement time (OR = 1.01, p = 0.002), pre-transplant endometrial thickness (OR = 1.24, p < 0.001), frozen–thawed embryo transfer (OR = 0.38, p < 0.001), blastocyst transfer (OR = 1.92, p < 0.001), and transfer of high-quality embryos (OR = 1.30, p = 0.002) were significantly associated with pregnancy outcomes. Multivariate analysis further clarified the independent effects of age (OR = 0.92, p < 0.001), severe degree of intrauterine adhesion (OR = 0.31, p = 0.001), endometrial thickness before embryo transfer (OR = 1.19, p < 0.001), blastocyst transfer (OR = 2.03, p < 0.001), and transfer of high-quality embryos (OR = 1.36, p = 0.001) on pregnancy outcomes.ConclusionAge, pre-transplant endometrial thickness, severe intrauterine adhesions, blastocyst transfer, and transfer of high-quality embryos are independent factors associated with pregnancy outcomes following intrauterine adhesion separation and subsequent embryo transfer.